2008
DOI: 10.2118/96021-pa
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Surfactant-Induced Interfacial Interactions at Reservoir Conditions

Abstract: The effect of surface-active chemicals on oil/water interfacial tension (IFT) and wettability in crude-oil/brine/rock systems at reservoir conditions is important in enhanced-oil-recovery (EOR) processes. However, most of the experimental studies on IFT and contact angles have been conducted at ambient conditions and using stock-tank crude oils. In this study, live and stock-tank crude oils have been used at reservoir conditions to make IFT and dynamic contact-angle measurements using the drop-shape-analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…From Table 4, it is observed that the potential change in the wettability of the reservoir rock shifted toward more water-wet condition. Therefore, this wettability change can increase the imbibition of water into the hydrocarbon reservoir, consequently optimizing the oil recovery (Xu et al 2008). This change in wettability is due to the fact that chelating agents dissolve minerals present inside the pore spaces as described by (Shafiq et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…From Table 4, it is observed that the potential change in the wettability of the reservoir rock shifted toward more water-wet condition. Therefore, this wettability change can increase the imbibition of water into the hydrocarbon reservoir, consequently optimizing the oil recovery (Xu et al 2008). This change in wettability is due to the fact that chelating agents dissolve minerals present inside the pore spaces as described by (Shafiq et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…They also concluded that altering wet ability by surfactants can result in enhanced oil recovery through decreasing capillary pressure and adhesive forces. [6] In their research about evaluation of lingosulfonates as an adsorbed material to be sacrificed (lost) during surfactant injection, Hong,S.A,Bac,J.H referred that the lost amount of surfactant can be significantly decreased (more than 50%) if an initial treatment by lignosulfonate wash is done. [7] Researcher Marc Baviere showed in his study about olefin sulfonate (AOS) behavior in high temperature and high hardiness as a surfactant in EOR that this sulfonate group gives important results especially at high temperatures and salinity, in addition to the chemical stability of this kind of Sulfonates.…”
Section: Reference Studymentioning
confidence: 99%
“…Surfactant is studied for improving water flooding in fractured reservoirs since it could change matrix wettability and/ or reduce water/oil interfacial tension (IFT) to enhance capillary imbibition and/or reduce residual oil saturation. The wettability alteration and IFT reduction are two main mechanisms of surfactant enhanced oil recovery (EOR) which depends on the oil/brine/rock system, the surfactant type and concentration, divalent ions, salinity, temperature and others (Standnes and Austad 2000;Standnes et al 2002;Babadagli 2002Babadagli , 2003Seethepalli et al 2004;Xu et al 2005;Alvarez and Schechter 2016;Golabi et al 2012;Alvarez et al 2014;Gao and Sharma 2013;Karnanda et al 2013).…”
Section: Introductionmentioning
confidence: 99%